2012
DOI: 10.1073/pnas.1117592109
|View full text |Cite
|
Sign up to set email alerts
|

Microbial interspecies electron transfer via electric currents through conductive minerals

Abstract: In anaerobic biota, reducing equivalents (electrons) are transferred between different species of microbes [interspecies electron transfer (IET)], establishing the basis of cooperative behaviors and community functions. IET mechanisms described so far are based on diffusion of redox chemical species and/or direct contact in cell aggregates. Here, we show another possibility that IET also occurs via electric currents through natural conductive minerals. Our investigation revealed that electrically conductive ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
307
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(315 citation statements)
references
References 42 publications
4
307
2
2
Order By: Relevance
“…Magnetite-mediated DIET has been directly demonstrated only in cocultures of Geobacter sulfurreducens and Thiobacillus denitrificans (45) and of G. metallireducens and G. sulfurreducens (44). To date, magnetite-mediated DIET has not been observed in defined syntrophic methanogenic cocultures.…”
Section: Fig 2 Xrd Spectra Of Ferrihydrite Incubated With Geobacter Mmentioning
confidence: 99%
“…Magnetite-mediated DIET has been directly demonstrated only in cocultures of Geobacter sulfurreducens and Thiobacillus denitrificans (45) and of G. metallireducens and G. sulfurreducens (44). To date, magnetite-mediated DIET has not been observed in defined syntrophic methanogenic cocultures.…”
Section: Fig 2 Xrd Spectra Of Ferrihydrite Incubated With Geobacter Mmentioning
confidence: 99%
“…Generally, microbial uptake of electrons from extracellular surfaces is a widespread and ecologically significant process in many environments (98)(99)(100)(101). In the context of microbial corrosion, it is particularly interesting to question the evolutionary roots and ecological significance of direct electron uptake.…”
Section: Who's Who In Srb-induced Corrosion? Phylogenetic Distributiomentioning
confidence: 99%
“…In addition to these anodic microbial processes, recent studies have revealed that some microorganisms can take up 'free' cathodic electrons from conductive minerals during interspecies electron transfer (Kato et al, 2012) or from abiotically reduced surfaces such as deep sea hydrothermal vent chimneys (Nakamura et al, 2010). This use of 'free' electrons as electron donor in microbial catabolism finds also relevance in engineered bioelectrochemical systems, which have been emerging as promising platforms for a sustainable energy landscape.…”
Section: Introductionmentioning
confidence: 99%